CODESRIA Bulletin Online, No. 10, May 2021: Why Development and Transformative Social Policy Matter: Lessons of COVID-19 in Africa: A lecture in honour of Thandika Mkandawire, delivered at the London School of Economics, 20 November 2020 - Jìmí O. Adésínà (CODESRIA Bulletin, 2021)
A lecture in honour of Thandika Mkandawire, delivered at the London School of Economics, 20 November 2020 Introduction I would like to start by expressing my appreciation to Prof. James Putzel, Prof. Duncan Green and the Department of International Development here at the LSE for the honour of this invitation. The department is home to several friends, and it was the academic home of a person to whom I owe a lot, Professor Thandika Mkandawire. Thandika would have been eighty years old on 10 October this year. He passed away on the 27 March 2020. Three people have been most influential in my academic journey. Omafume Onoge and John Ohiorhenuan were influential teachers and ndugu during my time as a student at the University of Ibadan. And then there was Thandika, whom I first met shortly after completing my doctoral studies. ‘He to me, was everything.’ Thandika was a veritable Mwalimu. Every encounter, every moment of breaking bread, was a time to behold the musing of a mind with immense capacity for observation and cutting through intellectual bull. From Thandika one learnt never to shirk from the cause of Africa. From him, we learnt how to be human. I present this lecture in his honour. The lecture is concerned with some of the lessons that we can learn from Africa’s experience of the COVID-19 pandemic. A public lecture imposes time constraint. For this reason, I have limited my focus to two sets of lessons: those concerned with the national responses to the livelihood impacts of the pandemic, and what the pandemic reveals about the crisis of structural transformation, research and the innovation ecosystem, and manufacturing capacity. I use these lessons to address why Development and Transformative Social Policy matter for Africa. The constraint of time also imposes a limit of country cases that can be used. In large part (though not exclusively), I have drawn on the cases of Nigeria and South Africa. The choice is not accidental. These are the two largest economies in Africa. The choice is also personal: I am Nigerian by birth and South African by domicile. COVID-19 Pandemic and Africa: some lessons According to the African Centres for Disease Control and Prevention, as of 14 November 2020, there were 1,965,485 reported cases of SARS-COV-2 infection across the continent, and 47,134 confirmed COVID-19 deaths (Africa CDC 2020). Africa accounted for 3.65 per cent of the global reported cases of SARS-CoV-2 infection, and 3.6 per cent of reported COVID-19 deaths. The southern Africa region accounted for 42.75 per cent of total reported cases, North Africa accounted for 32.32 per cent and West Africa 10.06 per cent. South Africa accounted for 89.15 per cent of the total reported cases in southern Africa, while Morocco and Egypt accounted for 62.76 per cent of the total confirmed cases in North Africa. In West Africa, Nigeria accounted for 32.85 per cent of the total confirmed cases. Figure 1: Regional Distribution of Confirmed SARS-CoV-2 Cases (14 November 2020) Source: Africa CDC (Voir PDF) Case Illustration: Nigeria and South Africa On 27 February 2020, Nigeria reported its first SARS-CoV-2 case. The index case was an Italian national who, two days earlier, flew into the country from Milan. At the time only Egypt and Algeria had reported cases of the new coronavirus infection. On Thursday 5 March 2020, South Africa reported its index case—a 38-year-old male who had travelled to Italy and had returned to South Africa on 1 March 2020 (NICD 2020). Figure 2 shows the trend in the confirmed cases (on a seven-day moving average) of confirmed SARS-CoV-2 infection, with South Africa reaching a peak of 12,587 cases on 20 July 2020 and Nigeria a peak of 642 confirmed cases on 3 July 2020. While the quantitative trend in the two cases differs significantly, both countries—like most other African countries—responded very quickly to the initial pronouncements of the WHO in January 2020 about the new coronavirus and moved rapidly to respond with the reporting of their index cases. Note that I refer to ‘confirmed cases’ because we can only talk in terms of the confirmed reported cases rather than actual prevalence rates or case fatality in a country. The testing rate is important in reported confirmed cases. In the second week of November 2020, SARS-COV-2 tests per thousand of the population stood at 3.42 in Nigeria (14 November). This was against 86.5 tests per thousand of the population in South Africa (15 November), 13.44 tests per thousand in Senegal (15 November) and 44.38 tests per thousand of the population in Rwanda (11 November) and Senegal (21 October). The test rate for Singapore was 695.15 per thousand of the population (Our World in Data 2020b). The test rate reflects a combination of testing capacity and institutional commitment to confront the pandemic, among other factors . While much has been made about the unreliability of case and fatality data from Africa, there is consensus that the pandemic has hit the continent much less than the initial projections suggested. And there has been the scramble, again, to explain the Africa Dummy. Some of these explanations have been gentle. The early response to the pandemic by several African countries, drawing on the previous experiences of dealing with epidemics—the most recent being the Ebola outbreak— has been used to explain the less than predicted infection and fatality rates of Covid-19. And there is the story of Africa’s youthful population as an explanation. But there have been more bizarre ideas. The high poverty rate and overcrowded shanty towns have been offered to explain the relatively low case and fatality rates (Harding 2020). It is a curious one. So, what might the policy advice to the UK government be from this proposition? If you want to deal with a raging pandemic, you should let poverty rise precipitously in your country and encourage the growth of slums and shanty towns? If the case and fatality impact might have been much less than predicted, the livelihood impact of partial or total lockdowns would have been more severe. I say ‘would have’ because we have little, in the way of firm and solid data, to make a precise determination. Figure 2: Daily confirmed cases of SARS-CoV-2 infection (South Africa and Nigeria). (Voir PDF) Source: Our World In Data 2020a, https://ourworldindata.org/coronavirustesting#world-map-total-tests-performed-relative-to-the-size-of-population. In a continent where micro enterprises (and the informal economy) represent a substantial share of the labour market, not being able to trade on a daily basis would impact, adversely, the livelihood of people who depend on daily receipts. With the adverse impact of lockdowns in sending countries, migrants’ remittances are projected to be affected. The World Bank claimed that ‘remittance flows to low and middle-income countries (LMICs) are projected to fall by 7 percent, to 508 billion in 2020, followed by a further decline of 7.5 percent, to 470 billion in 2021’ (World Bank 2020). The social policy architecture in place before the pandemic matters in the capacity of a country to respond to the livelihood challenges of the contraction of economic activities. Here, the limited available evidence suggests that the degree of informality within the economy, and the labour market in particular, will affect the exposure to the livelihood impact of public health mitigation measures and down-turn in economic activity. Even if public authorities are inclined to roll out livelihood mitigation measures, against the loss of income, the institutions may simply not be there to ensure the reach. Much of this, we would argue, has a lot to do with the model of social protection that the dominant international actors have actively pushed and merchandised over the past two decades: the residual, segregated, social assistance model. The COVID-19 pandemic also shows why inequality matters. The capacity of individuals to cope with restrictions on economic and social activities reflects the inequality of wealth and asset-holding, and labour market locations. It is easy to self-isolate when you live in a mansion; not so much when you are part of a family of five living in a single-room shack. It is easy to ride the short-term loss of income when you have significant discretionary resources stashed away in bank accounts; less so if you are an informal sector vendor who depends on daily revenue flows for survival. In this regard, Nigeria and South Africa are two of the four African countries with the highest wealth inequality, with South Africa at 84.0 and Nigeria at 81.4. Nigeria is the only non-southern African country on the list (Adesina 2016). Testing capacity, quality of care that medical outfits can provide, capacity to produce testing equipment and reagents, all point to the level and quality of pre-pandemic investment in the national system of innovation and national manufacturing capacity. Even at the much lower levels of the effects of the pandemic on cases and fatalities, the COVID-19 pandemic revealed important deficiencies in these areas of Africa’s capacity to respond. These are issues of Development, what we mean by Development, and the nature of the social policy architecture that undergirds a country’s welfare regime. Informality and Social Policy Response to the Pandemic The degree of informality of an economy and the labour market has implications for the development of social policy architecture. The proposition is that the reach of a national social insurance system is constrained by labour market informality. For Africa, this has been reinforced by the intense merchandising of segmented, stratified and segregated social policy (Fischer 2018) and the restraint of industrial policy that came as part of the neoliberal public policy project of the last four decades. The deepening of economic informality is itself a product of the reversal of the industrialisation project that was witnessed in the first two decades of the post-independence period. Figure 3: Size and composition of informal employment in Africa (2016) Source: Kiaga, Lapeyre and Marcadent, 2020 (Voir PDF) Figure 3 suggests that 89.7 per cent and 82.7 per cent of females and males, respectively, in Africa are in informal employment (including agriculture). There are, of course, regional and national variations. Nigeria and South Africa demonstrate such variation. Dell’Anno and Adu (2020) put the figure of Nigeria’s labour force employed in micro enterprises at 81.3 per cent in 2013. The 2020 third quarter labour force survey data for South Africa suggests that 16.72 per cent of South Africa’s labour force was employed in what the national statistical agency refers to as the ‘informal sector’ (StatsSA 2020). This excludes employment in the agricultural sector. Even if we add employment in ‘private households’, the highest share of informal employment would be 24.35 per cent. Technically, however, informal employment will be less than this figure considering that, where someone is employed in domestic work for more than 24 hours per month, this employment is subject to a minimum wage and unemployment insurance. Taken together with the social policy architectures of both countries, the structure of the labour market in Nigeria and South Africa would explain the differences in the social protection responses of Nigeria and South Africa. In Nigeria, a localised lockdown started on 30 March 2020, affecting Lagos State, Ogun State and the Federal Capital Territory. The primary social protection responses included a transfer in cash and a promised food pack for the ‘most vulnerable’ in the areas affected by the lockdown. The cash transfer involved a lump sum payment of NGN 20,000 to people already on the Household Uplifting Programme (HUP) that had been launched in September 2016. The social assistance programme was a condition, set by the World Bank and Switzerland, for Switzerland to return to Nigeria the USD 322 million of the ‘Abacha Loot’ lodged in Swiss banks. This ‘loot’ was part of what the former dictator, Sani Abacha, was believed to have siphoned from the country’s coffers. As of March 2020, the National Social Register, from which HUP beneficiaries are drawn, had on its roll 2.6 million households (about 11 million Nigerians). To get a sense of the generosity of the amount paid as cash transfer to mitigate the livelihood impact of the lockdown, the lump sum payment is the equivalent of NGN 333 per day. A 500g loaf of white bread in Lagos cost NGN 355 at the start of the lockdown. The food parcels were distributed sporadically in some of the states. The widespread looting of government warehouses as an adjunct to the #EndSARS protest movement in October 2020 was indicative of the sense of fairness and efficiency in the distribution of the packs. The #EndSARS protests were initially a revolt led by young people in protest at policy brutality. At the end of October 2020, another one-off cash payment of NGN 30,000 was announced. This was targeted at ‘artisans and self-employed individuals’. The scheme restricted the pay-out to 9,000 beneficiaries in each of the thirtysix states of the federation and the Federal Capital Territory. In South Africa, a national lockdown came into effect on 27 March 2020. The social protection measures to mitigate the livelihood impact involved three broad instruments. The first involved existing social grants. The Child Support Grant (CSG) was raised to ZAR 740 per child in May 2020. From June to October, the grant reverted to ZAR 440 per child, while caregivers of a child received ZAR 500 a month for the period of June to October 2020. This amount was regardless of the number of children in a household who received the grant. Recipients of all other grants received a top-up of ZAR 250 per month from June to October 2020. These grants covered 17 million beneficiaries, out of which about 12.5 million were CSG beneficiaries. While often mobilised within the international social assistance network as an example of ‘social protection’ worthy of emulation, South Africa’s social grant system is no poster child for poor-centric social assistance schemes. While eligibility involves means-testing, this is not targeted at ‘the poor’. In October 2019, for a child to qualify for the Child Support Grant, the income threshold for the caregiver was ZAR 4,300 per month (SASSA 2019). The Upper Bound Poverty Line for 2019 was ZAR 1,227 (StatsSA 2019). In addition to the top-up of the social grant, a new Special COVID-19 Social Relief of Distress Grant was introduced for those who were normally not recipients of any of the existing social grants. The benefit level was ZAR 350 per month. Initially intended to run until October 2020, this special grant has now been extended to January 2021. Again, to apply our earlier measure of generosity, the special relief grant translates to ZAR 11.66 a day, or less than the cost of a 500-gram loaf of white bread. Like Nigeria’s HUP-based COVID-19 mitigation measure, the Social Relief of Distress Grant reflects the dominant vision of public social provisioning in the so-called international development circles. It comes with a diminished vision of an acceptable level of human wellbeing. The grant was benchmarked against the national food poverty line (Ramaphosa 2020). However, in 2019, the food poverty line was ZAR 561 a month (StatsSA 2019: 3). A third instrument, concerned with protecting jobs, was the Temporary Employee/Employer Relief Scheme (TERS). The scheme was implemented under the national Unemployment Insurance Fund—a contributory social insurance scheme that covers income loss while unemployed for a limited period. It is a national social insurance housed at the national Department of Employment and Labour. In March 2019, the net asset of the UIF was ZAR 144.26 billion (UIF 2019). TERS compensates employers who are unable to pay the full salaries of their employees, and employees who were furloughed could apply to the scheme. Claims under the scheme were capped at ZAR 17,712.00 per month, per employee. As of 27 October 2020, over ZAR 51 billion had been paid to one million companies, disbursed in over 11.5 million payments (Buthelezi 2020). It is difficult to imagine that the UIF could have played the role it did in protecting jobs and livelihoods if it had been designed around market-based insurance models. Its strength and relevance lie in being a publicly managed national social insurance scheme. The structure of the South African labour market and the space for social insurance for 70 per cent of those in the labour market allows the institutional basis and a national social insurance to support livelihoods at a much higher level than what is offered to those supported through social assistance measures. R&I and manufacturing deficits In March 2020, news emerged that researchers at the Institut Pasteur de Dakar in Senegal had developed a rapid diagnostic kit for SARSCoV-2 (new coronavirus), which would cost about USD 1 and produce results in a matter of minutes, not hours. Senegal and the institute have accumulated considerable experience in dealing with epidemics in the past, the latest being the Ebola epidemic. Like many other African countries, experience of dealing with earlier cases of epidemic came into play in the mitigation and control of the COVID-19 pandemic. The diagnostic kit is being developed and validated in partnership with other research entities around the world, the most prominent of which is the UK’s Bedfordshire-based Mologic. While most news outlets and the researchers at the Institut Pasteur de Dakar claim the development of the kit as largely their innovation, Mologic claims on its website that it: Is working in close partnership with the Institut Pasteur de Dakar to validate and manufacture the COVID-19 test at a new manufacturing site, DiaTropix, in Senegal. This will be the first time that a diagnostics kit created in the UK will be jointly manufactured in Africa, to ensure its immediate availability, to manage any potential outbreaks on the continent, and further international spread. (Mologic 2020) While international collaboration is important for scientific efforts, the Institut Pasteur’s tie-up with Mologic betrays once again the crisis of dependence and intellectual/ scientific sovereignty, in which Senegalese researchers are likely to be reduced to junior partners. Much of this has to do with investment in, and building, national research and innovation capacity, within the framework of a national sovereign project. The underfunding of innovation infrastructure turned into defunding in the wake of first-wave neoliberalism—à la Structural Adjustment Programme. The validation of the diagnostic test kit is being undertaken in the UK, not Senegal. The issue is not if African scientists are capable of innovation. The concern is the denuding of the broader infrastructure that a national system of innovation requires for an autonomous and sovereign functioning. Similarly, scientists at the Nigerian Institute of Medical Research, in Lagos, developed the SARSCoV-2 Isothermal Molecular Assay (SIMA) kit, which is ten times less expensive than the standard PCR test and will produce results in under forty minutes (Medical Brief 2020). The reagents used in the SIMA test kits still needed to be imported from the UK (Lawal 2020). The validation of the test kit would still depend on research establishments in Europe. Nigeria imports much of its test kits and personal protection equipment from China. South Africa, with more depth of manufacturing capacity and support for the national system of innovation, was for much of the first eight months of the pandemic importing diagnostic test kits. In July 2020, the Minister of Higher Education and Innovation made seven awards, totalling ZAR 18 million, to seven local companies ‘in order to ramp up the country’s ability to produce locally developed reagents and test kits for COVID-19’ (Nzimande 2020). The companies had ‘six months to begin production’. Early in the pandemic, the African Union established the Africa Medical Supplies Platform to coordinate the acquisition of medical supplies. The facility helps member states to acquire medical resources at bulk price. The PCR test kits being offered on the platform are imports from India, the USA, vendors in Lyon, France, etc. The absence of autonomous manufacturing capacity and dependence is glaring. The above is indicative of deficiencies in manufacturing capacity, national systems of innovation and the associated ecosystem necessary for immediate response to external shocks such as the pandemic. Perhaps, nothing signifies the crisis of investment in national system of innovation as much as the vaccine story. As far as I can tell, there is no current candidate vaccine emerging out of Africa. Of the forty-eight candidate vaccines in different clinical trial stages, over twelve are from companies and research outfits based in China, four in India, three in South Korea (if you count the International Vaccine Institute), two in Australia, one each in Singapore, Taiwan, Cuba, Japan, Kazakhstan. The rest are research entities based in Europe and North America (Sky News). Again, the COVID-19 pandemic highlights the crisis of maldevelopment and what Mkandawire referred to as the maladjustment of Africa. The maladjustment is not simply of its economies, but its society, its labour market and its systems of innovation. The consequences of this are apparent in what Jayati Ghosh refers to as ‘vaccine apartheid’ (Ghosh 2020). Within days of Pfizer/BioNTech announcing the first successful vaccine development, we were already seeing vaccine hoarding. ‘Within days of its announcement,’ Ghosh notes, ‘Pfizer had sold more than 80% of the vaccine doses it will be able to produce by the end of next year to governments representing only 14% of the global population’ (Ghosh 2020). The same vaccine hoarding is equally playing out with the candidate vaccines from Moderna, Johnson & Johnson, and AstraZeneca. Even if Africa and other ‘developing’ countries gained access to vaccines through the COVID-19 Vaccine Global Access Facility (COVAX) it would be from a position of weakness and dependence. The point about the lessons that we can draw from Africa’s experience of the COVID-19 pandemic is that Development matters. So does Transformative Social Policy. Why Development and Transformative Social Policy Matter Over a decade ago, at the Inaugural Lecture that he delivered at the London School of Economics, Thandika Mkandawire made a distinction between the ‘Truman’ and the ‘Bandung Conference’ versions of the post-World War II development discourse (Mkandawire 2011: 7). In the Truman take on development, in which ‘international development’ is mired, development is ‘the moral premise for helping “distant strangers”,’ (ibid.) with its attendant paternalism. The dominant version of thinking in ‘international development’ has, in the wake of what John Toye (1987) refers to as the ‘counterrevolution’, denuded Development of strategic planning and industrial policy. In its place Development has become more concerned with microeconomic processes of ‘human development’ and the relief of poverty. In pursuit of this diminution of what Development means, vast areas of the African continent have been turned into spaces of open laboratory experiments, with the methodology of randomised control that says a lot about little. Giving ‘money to the poor’ was declared ‘a silent (or quiet) revolution’ in development (Barrientos and Hulme 2009; Hanlon, Barrientos and Hulme 2010). Barbara Harris-White (2006) has aptly described the ‘new poverty agenda’ as an ‘impoverishment of the concept of development’. At the April 2010 lecture, Mkandawire offered a vision of development grounded in the Bandung Spirit. Development involves growth with structural transformation of economy and society, the mastery of technology and strong manufacturing capacity. ‘Catching up’, a phrase Thandika had no problem using, ‘requires that countries know themselves and their history that has set the “initial conditions” for any future progress’ (Mkandawire 2011: 13). Development requires learning from the pioneers, but it is not mimicry. The knowledge imperative requires considerable investment in institutions of knowledge production and state capacity—the capacity to coordinate and steer the development process. This involves a sustained ecosystem of innovation and capacity to respond to a broad range of challenges. Structural transformation and mastery of technology goes with strong and innovative manufacturing capacity. In the Bandung Spirit, Development is, in the words of Samir Amin, also grounded in a national sovereign project. It is a quest for averting the extraversion of economy, culture and knowledge systems that is inherent in the nature of imperialism. What we learn from the COVID-19 pandemic is the urgency of Africa’s quest for development in the sense that Mkandawire understood it and underpins Africa’s Agenda 2063. Africa’s development path cannot be subject to the discursive constraint from the West, but neither can it rely on the earth-depleting models of the West’s history of structural transformation. When the President of the European Association of Development Research and Training Institutes, in a recent blog, calls for ‘overcoming developmentalism’ (Melber 2020) and the article is accompanied by the image of a smouldering urban refuse dump, it is important to retort that what the image signifies is not an uncompromising commitment to development. What it signifies is maldevelopment (Amin 2011). A second component of Thandika’s thinking on development is that African states not only have to be developmental, but they also have to be democratic and inclusive (Mkandawire 2006a, 2007); ‘developmental’ in the sense of managing the economies ‘in a manner that maximises economic growth, induces structural change, and uses all available resources in a responsible and sustainable manner in highly competitive global conditions’ (Mkandawire 2007: 680); ‘democratic’ in the sense of being embedded in deliberative governance and a respect for people’s rights; socially ‘inclusive’ in providing ‘all citizens with a decent living’ (ibid.). At the heart of both enabling socioeconomic development and ensuring equity is the idea of Transformative Social Policy. This is a conceptual and evaluative take on social policy that emerged out of the multinational Social Policy and Development research programme that Thandika led as the Director of the United Nations Research Institute for Development (UNRISD). At the heart of the framework is a question that Thandika posed at the onset of the research programme: What questions does a country ask of its social policy in the context of development? Transformative Social Policy emphasises the complementarity of economic and social policy, highlights the multiple tasks of social policy, and insists on the deployment of social policy for ensuring equity and inclusivity in the development process. Thandika identified four tasks of social policy (production, protection, reproduction and redistribution) (Mkandawire 2006b). I have argued for a fifth task of social policy—that of social cohesion or nation-building (Adesina 2011, 2015). It is not that Thandika was unaware of the importance of social cohesion. It is that it did not feature in the primary tasks he attributed to social policy. Further, that social policy for inclusive development has to be underpinned by the norms of solidarity and the pursuit of equality (and equity). Transformative Social Policy is concerned with the transformation of the economy, social relations and institutions. It is concerned with mitigating the disruptive impact of the development process itself. Central to the transformation of social relations is the transformation of gender relations. What has been evident in the ‘social assistance’ response—the segregated, residual, public social assistance—is that it is grossly inadequate in mitigating the livelihood impact of the pandemic. A social assistance package that is sufficient to buy a loaf of bread may keep hunger at bay, but it does little else. Yet, the Social Relief of Distress grant has become a cause célèbre within the Basic Income civil society campaign in South Africa. A wider vision of human wellbeing requires broader instruments. Building social cohesion and a more equal society is important for how society copes with external shocks. Social cohesion that builds trust between state and society and within society allows for a more cohesive response to a pandemic—one that does not turn the non-wearing of a mask in a pandemic into a political statement of defiance. Social cohesion nurtures the norms of ‘other-regarding’ in which not catching a virus is as important as not passing it on. I end on this note: at the heart of the imperative of development, underpinned by transformative social policy, is Mwalimu Nyerere’s pivotal idea of the defence of, and respect for human dignity. Thank You.